Preoperative Right Ventricular Free‐Wall Longitudinal Strain as a Prognosticator in Isolated Surgery for Severe Functional Tricuspid Regurgitation - Kim, Minkwan (J Am Heart Assoc, 2021)
BACKGROUND: Severe tricuspid regurgitation (TR) should be intervened before the development of irreversible right ventricular (RV) dysfunction. However, current guidelines do not provide criterion related to RV systolic function to guide optimal surgical timing. We investigated the prognostic value of RV longitudinal strain in patients undergoing isolated surgery for severe functional TR. METHODS AND RESULTS: We enrolled 115 consecutive patients (aged 62±10 years; 23.5% men; 62.6% [n=72] with previous left‐sided valve surgery) who underwent isolated surgery for severe functional TR at 2 tertiary centers. Preoperative clinical and echocardiographic parameters, including RV free‐wall longitudinal strain (RVFWSL), were collected. The primary end point was a composite of cardiac death and unplanned readmission attributable to cardiovascular causes 5 years after surgery. Forty patients (34.8%) reached the primary end point during 333 person‐years of follow‐up. There were 11 cardiac deaths and 34 unplanned readmissions attributable to cardiovascular causes, with 5 patients experiencing both. An absolute preoperative RVFWSL <24% was associated with the primary end point (hazard ratio, 2.30; 95% CI, 1.22–4.36; P=0.011), independent of clinical risk factors, including European System for Cardiac Operative Risk Evaluation II and hemoglobin levels. Meanwhile, other conventional echocardiographic measures of RV systolic function were not significant. The addition of an absolute RVFWSL <24% provided incremental prognostic value to the clinical model for predicting the primary end point. CONCLUSIONS: Preoperative RVFWSL as an indicator of RV dysfunction was an independent prognosticator in patients undergoing isolated surgery for severe functional TR. Thus, preoperative RVFWSL could help determine the optimal surgical timing for severe functional TR.